Alguns caminhos da educação ambiental em escolas de ensino fundamental da rede municipal de Araraquara/SP - Ventorin, Araceli Pedroso (2019)
The environmental problem affects the lives of billions of people and, given the magnitude with which it has presented itself, arouses worldwide concern. In this context, Environmental Education (EE) plays an important role in the formation of committed subjects in the search for solving social and environmental problems or alternatives to the current development model. Considering that multiple political and ideological influences have shaped EE, we cannot refer to it in the singular, since there are several possible ways to conceive and practice it (CARVALHO, 2004; LAYRARGUES; LIMA, 2014). Thus, this study aimed to analyze the different modalities of EE existing in elementary schools of the municipal network of Araraquara, São Paulo, in order to discuss its specificities, potentialities and challenges. In this network, EE processes take place in an interdisciplinary manner, in Common Base disciplines, and through special discipline, from the diverse part of the curriculum. Data were collected through field research in three school units: one full-time elementary school, one part-time elementary school, and one full-time education center that serves students in the regular school counter-shift. We conducted semi-structured interviews with teachers and pedagogical coordinators, document analysis of the schools involved and the Municipal Secretariat of Education, in addition to the municipal legislation establishing the Municipal Environmental Education Program. The results were analyzed through elements of content analysis and organized in four axes: “Working with EE in school units”, “Perspectives and trends of EE in the EUs”, “EE as a discipline” and “Teacher Training “We find that there are EE processes going on in this network, although under different organizations and which are mostly between the conservationist and pragmatic macrotendencies (LAYRARGUES; LIMA, 2014), and that although there is ongoing work in EE workshops of two school units investigated, the continuity of the work alone does not guarantee a critical perspective in its development. We consider the formation of teachers to work in this perspective as fundamental, as well as the improvement of the “Municipal Environmental Education Program”. Faced with existing challenges, both in interdisciplinary work and workshops, we understand that there is potential for conducting a critical EE work, taking the debate on environmental issues beyond the discussion on whether or not a discipline.